GEOCHEMISTRY AND ISOTOPIC COMPOSITION OF MANTLE XENOLITHS FROM MT. VULTURE VOLCANO, S. ITALY - Kostoula, Thomai; Jones, Adrian; Downes, Hilary; Beard, Andy (Ofioliti, 1999)
Mt. Vulture volcano is located at the eastern margin of the Apennines, S. Italy and belongs to the Intra- mountain Ultra-alkaline Magmatic Province (Stoppa & Lavecchia , 1993). It is composed of Recent tephrites, basanites, phonolites and melilitites (De Fino et.al, 1982). Mantle xenoliths are found in the youngest unit of the volcano, a sequence of melilititic and carbonatitic tuffs. They are very fresh, mainly lherzolites and wehrlites. A few harzburgites and orthopyroxene (En89, Wo 2.0), clinopyroxene (Mg# 90-92, Al2O3 = 3-6 wt%, Cr2O3% ~1%) and one composite xenolith have also been found. The main mineral phases are olivine (Fo 90- 92), Cr-spinel ( MgO = 12-20 wt%, Cr2O3 = 30-40 wt%). Glasses are frequently found and are thought to represent in situ partial melting. Mica (phlogopite) is found in a few xenoliths. Carbonate is also present occasionally. The xenoliths have been derived from a depth between 55-75 km, corresponding to the spinel stability field in the upper mantle (Jones et. al., subm.).In this paper we present the geochemistry and isotope composition of the Vulture xenoliths. A selection of representative samples have been analysed for Sr, Nd isotop eratios. ICP-MS analyses on clinopyroxenes and whole rock powders have also been performed. The REE patterns for Cpx from Vulture peridotites show a slight to modest enrichment in LREE. (Ce/Yb)n values are relatively low (<5) and mainly < 1. The more LREE-enriched rocks are the wehrlites with (Ce/Yb)n >1. Sm/Nd is lower in the LREE - enriched samples. There is a positive correlation between enrichment in LREE and degree of deformation: the more deformed xenoliths have greater amounts of LREE than the less deformed ones. This is in consistence with the results from other xenolith localities in Europe (e.g., Hungary, France, Germany) (Downes, 1990). The LREE enriched rocks have equilibrated at higher pressures (~20 kbar) than the depleted xenoliths (15-18 kbar) but there is no apparent correlation with temperature.The isotope results give the following range for 87Sr/86Sr: 0.70424 - 0.70580 and for 144Nd/143Nd: 0.51258 - 0.51280. The eSr values vary between -3.7 and +18.5, with the majority of the samples having positive values >7. eNd is positive for all the xenoliths except for one, with a range from -1.17 to + 3.12. Only one sample shows a strongly depleted isotopic signature having the highest eSr (+18) and the lowest eNd (-1.17) amongst the xenoliths. The positive eNd along with the higher Sr - lower Nd relationship indicates that the xenoliths originated in a depleted mantle that has been affected by enrichment processes only recently. This is also supported by the fact that some samples, although being LREE-enriched, have Sm/Nd < CHUR (0.325). The source of the enrichment could be either a hydrous fluid and / or a carbonatitic melt. There is no strong evidence to allow us to exclude either possibility. However, petrographical features of the xenoliths, e.g. a lherzolite with a wide zone of recrystallised wehrlite that is believed to be the product of reaction between a carbonatite melt and the peridotite (Jones et. al., submitted) can support a carbonatite as the LREE-enrichment agent. A weak correlation between isotope chemistry and equilibration conditions is observed with a tendency for the higher 87Sr/86Sr - lower 144Nd/143Nd samples to have equilibrated at higher pressure (18-20 kbar) and temperature (~1100oC). In comparison with other isotopic data on xenoliths from Europe, Vulture xenoliths have generally higher 87Sr/86Sr and they fall in the end of the high 87Sr/86Sr - low 144Nd/143Nd array having an Ocean Island Basalts-type isotopic signature. The Vulture host rocks are more enriched in 87Sr/86Sr but they have similar low 144Nd/143Nd (Vollmer, 1976; Hawkesworth and Vollmer, 1979).The geochemistry and isotopic compostition of the mantle xenoliths show that the sampled mantle beneath Mt. Vulture volcano has been originally depleted in LREE and LILE but has undergone a recent slight enrichment. The metasomatic agent is probably a carbonate melt but the possibility that hydrous fluids may have also contibuted to the process cannot be ruled out. Geothermobarometry and geochemistry tentatively suggest that the LREE- and LILE-enriched xenoliths have been derived from greater depth than the depleted rocks. This could be reflection of a stratigraphic division witihin the lithospheric mantle, with a fertile domain underlying the refractory domain.